A New Demonstration of the Illusory Letters Phenomenon: Graphemic Restoration in Arabic Word Perception. (February 2015) - Jordan, Timothy R; Sheen, Mercedes; AlJassmi, Maryam A; Paterson, Kevin B
The illusory letters phenomenon (ILP) is a unique demonstration that words can be perceived as complete even when letters are physically absent. However, the ILP has only ever been reported for a Latinate language (English), and it is unknown whether the illusion occurs for alphabetic languages with fundamentally different visual properties. Here we report a demonstration of the ILP for Arabic in which stimuli containing only the exterior letters of three-letter Arabic words and a nonsense pattern in the interior position were presented to fluent Arabic readers. Despite being incomplete, participants perceived these stimuli as complete Arabic words with all letters visible in their appropriate positions, and were unable to distinguish between illusory and normal displays. This finding provides an important extension of the original ILP and suggests that alphabetic languages may be widely susceptible to the phenomenon and reading generally may occur as a process augmented by illusory percepts.